Estudo epidemiológico sobre associação entre exposição à violência em diferentes fases da vida e a presença de transtornos mentais em adultos - Melo, Givanya Bezerra de (2015)
The study aimed to analyze the association between exposure to violence and the presence of mental disorder in the population aged 18 or more in the neighborhood of Benedito Bentes, Maceió / Alagoas. Epidemiological population-based study of analytical and cross-section, with a pure probability sample of 872 people in a cluster sampling. Data collection in the period from january 26 to march 2, 2015, with residents interviewed in the referenced households. The sociodemographic questionnaire, the Mini International Neuropsychiatric Interview and the Instrument Socioeconomic Stratum were used. The ethical aspects are met. Was obtained prior approval from the Ethics Committee of the Federal University of Alagoas, opinion n.º 608 613. We used the statistical package IBM Statistical Package for Social Sciences (S.P.S.S.) for Windows version 17.0, for statistical analysis, with a 95% confidence interval. In the results, 74.9% of respondents were female, 73.7% of blacks, 7.4 years of study average. The violence against children was prevalent in 12.4%, violence in adulthood by 19.6%, witnessing violence in life and 50.5% triple exposure to violence in 4.1%. Violence in childhood and in adulthood occurred mostly in the victim's home. Suffer violence in childhood was associated with lower socioeconomic status. The non-nuclear family structure was a protective factor for violence in childhood, adulthood or triple. Exposure to violence in childhood was associated with most disorders, with five times more likely to panic attack symptoms with limited; sexual violence in childhood was associated with four times the suicide risk of chances. Suffer violence as an adult was associated with a greater number of disorders, with six times more likely to abuse alcohol. Witnessing violence was associated with some of the disorders, with less force in the associations except substance dependence, with six times more likely. The triple exposure to violence was associated with fewer disorders than those who have experienced violence in adulthood; however, the combinations were more intense, thereby indicating whether the dose- response effect. Most outbreaks of violence demonstrated association with risk of suicide. Victims of sexual violence in childhood or adulthood had more than three times as likely to more risk of suicide. The posttraumatic stress disorder (PTSD) has been associated with sexual violence in adulthood, with ratio greater chances to eight times; there were no significant associations between sexual violence in childhood and PTSD. Exposure to violence was associated with higher chances of manifestation of disorders and suicide risk. There is a pressing need for early identification of victims of violence to offer appropriate psychosocial support. Violence should be a condition investigated in people with disorders history. Managers and health professionals articulated with other sectors need to discuss in amplified form the interrelationship between violence and mental health field in order to propose convergent interventions to local needs.